Sedimentation behavior of flocculant-treated soil slurry - He, Jia (2017)
Soil slurry dredged from seabed is becoming more widely used in land reclamation projects. A major problem encountered is that soil slurry is very high in water content and the dewatering process is difficult and time consuming. In this paper, the use of chemical flocculant for the dewatering of soil slurry is proposed and experimentally tested. Polyacrylamide (PAM) with different charge types/charge densities was tested in preliminary slurry dewatering tests. The results showed that the most effective flocculant, cationic PAM (CPAM) with +15 charge density, can reduce the volume of soil slurry (500% water content) by around 60% in 10 minutes. In contrast, the volume of pure soil slurry was almost unchanged. Slurry sedimentation tests on slurries with different flocculant contents and water contents were conducted. It is shown that, by adding flocculant into soil slurry, the rate of settlement under self-weight can be considerably increased in the tested range of water contents (100.7–879.5%). But the water content at the final state increases with flocculant additions. Slurry sedimentation curves displayed different characteristics with different flocculant contents as well as water contents. It is evidenced by particle size analysis that the addition of flocculant into soil slurry can attract soil particles and form large flocs (assemblage of particles), which explains the faster settlement rate in flocculant-treated soil slurry as compared with pure soil slurry. Scanning electron microscopic analysis revealed that flocculant-treated soil particles are more randomly oriented, while soil particles with no flocculant addition deposit in a more paralleled manner. This could explain the higher water content of flocculant-treated soil slurry at the final state.